2020
DOI: 10.1186/s13567-020-00802-z
|View full text |Cite
|
Sign up to set email alerts
|

Climate change implications for the distribution of the babesiosis and anaplasmosis tick vector, Rhipicephalus (Boophilus) microplus

Abstract: Climate change ranks among the most important issues globally, affecting geographic distributions of vectors and pathogens, and inducing losses in livestock production among many other damaging effects. We characterized the potential geographic distribution of the ticks Rhipicephalus (Boophilus) microplus, an important vector of babesiosis and anaplasmosis globally. We evaluated potential geographic shifts in suitability patterns for this species in two periods (2050 and 2070) and under two emissions scenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 59 publications
4
21
2
3
Order By: Relevance
“…Species-distribution modeling (SDMs) or ecological-niche modeling (ENMs) should be considered to be used as essential tools for identifying the priority areas for effective biodiversity conservation [44,95]. Previous studies show a relatively good performance of climatic variables to capture biodiversity distributions over space and time-i.e., climate-only models [44,65]. Here, we apply the ENMs to the national-to-regional level by conducting species-specific distribution models for 51 endangered primate species using bioclimatic covariates to identify priority areas for primate conservation in Indonesia and produce the alpha diversity maps for focal Indonesian primates, using stackedspecies-distribution models (S-SDM; [82]), also known as categorical species richness [81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species-distribution modeling (SDMs) or ecological-niche modeling (ENMs) should be considered to be used as essential tools for identifying the priority areas for effective biodiversity conservation [44,95]. Previous studies show a relatively good performance of climatic variables to capture biodiversity distributions over space and time-i.e., climate-only models [44,65]. Here, we apply the ENMs to the national-to-regional level by conducting species-specific distribution models for 51 endangered primate species using bioclimatic covariates to identify priority areas for primate conservation in Indonesia and produce the alpha diversity maps for focal Indonesian primates, using stackedspecies-distribution models (S-SDM; [82]), also known as categorical species richness [81].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we used 15 of the 19 variables of bioclimatic data to capture environmental covariates that represent a fundamental niche in the current condition, retrieved from WorldClim v.2.0 [62,63]. We excluded four covariates that combined precipitation and temperature information because they produced spatial artefacts [64,65]. To capture future climatic conditions, we used outputs from 19 global climate models (GCMs) based on CMIP5 data (Table S3)-i.e., coupled model intercomparison project phase 5, statistically downscaled using Delta methods [66].…”
Section: Environmental Covariatesmentioning
confidence: 99%
“…The temperature range where R. microplus tick was recorded in Burundi was 18-21˚C. Precipitation seasonality and relative humidity were also identified as important climate factors affecting R. microplus life cycle and tend to increase the number of tick generations and thus population dispersal [27,28]. Rhipicephalus microplus ticks require high rainfall although some variations were reported between season [27], although high proportion of ticks in areas of low rainfall between May and October in Africa have also been recorded [26].…”
Section: Plos Onementioning
confidence: 99%
“…Several recent publications have demonstrated how climate change can alter the distribution of vector-borne diseases transmitted by ticks, sandflies and mosquitoes. These studies investigate how changes in spatial distribution of arthropod vectors may influence future spatial distributions of vector-borne pathogens (Balasubramanian and Nikhil, 2015;Balasubramanian et al, 2019b;Balasubramanian et al, 2021;Medlock and Leach, 2015;Marques et al, 2020). Previous studies have shown that the season of the year and the field environment in which the ticks oviposit are important extrinsic factors as ticks were observed to produce a more significant number of eggs during peak and retreating of rains and when placed in the shade (Danielova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%